An annual-resolution stable isotope record from Swiss subfossil pine trees growing in the late Glacial. (1st November 2020) - Pauly, Maren; Helle, Gerhard; Büntgen, Ulf; Wacker, Lukas; Treydte, Kerstin; Reinig, Frederick; Turney, Chris; Nievergelt, Daniel; Kromer, Bernd; Friedrich, Michael; Sookdeo, Adam; Heinrich, Ingo; et al.
Abstract: Previous studies have suggested that the Late Glacial period (LG; ∼14 600–11 700 cal BP) was characterised by abrupt and extreme climate variability over the European sector of the North Atlantic. The limited number of precisely dated, high-resolution proxy records, however, restricts our understanding of climate dynamics through the LG. Here, we present the first annually-resolved tree-cellulose stable oxygen and carbon isotope chronology (δ 18 Otree, δ 13 Ctree ) covering the LG between ∼14 050 and 12 795 cal BP, generated from a Swiss pine trees ( P. sylvestris ; 27 trees, 1255 years). Comparisons of δ 18 Otree with regional lake and ice core δ 18 O records reveal that LG climatic changes over the North Atlantic (as recorded by Greenland Stadials and Inter-Stadials) were not all experienced to the same degree in the Swiss trees. Possible explanations include: (1) LG climate oscillations may be less extreme during the summer in Switzerland, (2) tree-ring δ 18 O may capture local precipitation and humidity changes and/or (3) decayed cellulose and various micro-site conditions may overprint large-scale temperature trends found in other δ 18 O records. Despite these challenges, our study emphasises the potential to investigate hydroclimate conditions using subfossil pine stable isotopes. Highlights: Millennial stable isotope chronologies of δ 13 C and δ 18 O from 27 Swiss subfossil pine trees, covering the Late Glacial (∼14 050–12 795 cal BP). Two extreme δ 18 Otree depletions parallel North Atlantic 'cool periods' (GI-1c, GS-1), another LG event (GI-1b) is not expressed in δ 18 Otree . Trees with less extensive decay have significantly higher inter-isotope (δ 18 Otree : δ 13 Ctree ) correlations.